PREDIKSI KEBERLANGSUNGAN PERUSAHAAN SUB SEKTOR HOTEL, RESTORAN DAN PARIWISATA DI ERA PANDEMI COVID-19 - Ni Luh Putu Uttari Premananda (UHN IGB Sugriwa Denpasar, 2021)
Predicting business continuity is very important because it will describe the financial condition of the hotel, restaurant and tourism sub-sector companies affected by the COVID-19 pandemic. A total of twenty-nine (29) hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange in 2020 became the object of research. In assessing the sustainability of the company, this study uses a modified Altman Z-Score model, which consists of four (4) ratios. These ratios include: working capital divided by total assets, retained earnings divided by total assets, EBIT divided by total assets, and book value of equity divided by book value of liability. From this model, the Z-Score value of each company will be obtained, which is then categorized into Healthy, Vulnerable, and Bankrupt Potential categories. This research shows that, of the 29 companies tested, 12 of them are in the Healthy category, 4 companies are in the Vulnerable category and 13 companies are in the Bankrupt Potential category. Prediction of business continuity is carried out so that the company can find out as early as possible the potential for bankruptcy and minimize this potential in the future. This prediction also helps managers in assessing the company's performance and operations, and determining whether the company has performed well or not. Future research can test the same model in other sectors on the IDX, and also on hotels,restaurants and tourism sub-sector companies in companies that have not been listed on the IDX.